Isolated ileal ganglioneuromatosis in an 11-year-old boy: Case report and review of literature - Subhashis Mitra; Sanghamitra Mukherjee; Hema Chakraborty (Wolters Kluwer Medknow Publications, 2016)
Ganglioneuromatous proliferation in the gastrointestinal tract is a rare occurrence and is usually associated with specific syndrome complexes such as multiple endocrine neoplasia Type 2B or von Recklinghausen's disease. We report here a case of diffuse intestinal ganglioneuromatosis, presenting as intestinal obstruction and chronic constipation in an 11-year-old boy. Sporadic cases of intestinal ganglioneuromatosis in the absence of any systemic manifestations are a very rare cause of enteric motility disorders in childhood, and we discuss the pathological and clinical significance of this finding. Histopathological identification of this uncommon cause of a common pediatric problem is important since the condition is amenable to surgical treatment.